Cellulose nanofiber-dispersed thermoplastic resin reinforced material
By immersing cytotin nanofibers and thermoplastic resin into fabrics or non-wovens, a dispersed thermoplastic resin reinforcement material is formed, which solves the problems of improving static and impact strength of CFRP and the difficulty of controlling CNF dispersion, and realizes lightweight, high elasticity and low-cost material production.
Patent Information
- Application Number
- JP2023145538
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-03-19
- Estimated Expiration
- 2043-09-07
AI Technical Summary
In the prior art, carbon fiber reinforced plastics (CFRP) are difficult to further improve static strength and impact strength during application, and the dispersion control of cytotin nanofibers (CNF) in matrix resins is difficult, resulting in increased production costs and time.
By immersing the cytotin nanofibers and thermoplastic resin into the fabric or non-woven fabric, a cytotin nanofiber dispersed thermoplastic resin reinforcement material is avoided, and the production process is simplified.
It is realized that without undergoing cytokinin nanofiber hydrolysis treatment, a lightweight, high elastic and low-cost thermoplastic resin reinforced material has excellent elastic modulus, and reduces dependence on carbon fiber reinforced plastics and reduces resource consumption.
Abstract
Description
[Technical field]
[0001] The present invention relates to a cellulose nanofiber-dispersed thermoplastic resin reinforced material. [Background technology]
[0002] From components for automobiles and aircraft to sporting goods, carbon fiber reinforced plastics (CFRP) are increasingly being used in products that require lightness and strength. For example, in sporting goods, there is a demand for "lighter and stronger materials," and the use of lightweight, high-strength CFRP is progressing. However, for example, in bats, cracks occur on the surface and inside of the CFRP when the ball is repeatedly struck, so the CFRP layer is made thicker to increase static strength and impact strength. In these products, if the static strength and impact strength of CFRP are improved by 20%, it can be made thinner, and the weight can be reduced by 15 to 30%, allowing users to feel a much lighter swing feeling. However, it is difficult to further improve the static strength and impact strength of CFRP in this way.
[0003] Cellulose nanofibers (CNFs) are environmentally friendly nanofibers that can be refined from wood and other materials, and are lightweight and strong at the same time. However, it is very difficult to control the dispersion of CNFs in the base resin, and hydrophobic modification techniques and the use of organic solvents are generally considered to be the solutions. For this reason, it is generally considered difficult to apply CNFs to CFRP without hydrophobizing them.
[0004] Therefore, Patent Document 1 shows that by constructing a cellulose nanofiber layer on at least one side of a carbon fiber reinforced plastic layer, in other words, by constructing the carbon fiber reinforced plastic and the cellulose nanofiber as separate layers, the resulting material is lightweight and has excellent impact strength. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2019 / 221155 Summary of the Invention [Problem to be solved by the invention]
[0006] In Patent Document 1, the material is reinforced by providing a cellulose nanofiber layer, but laminating the carbon fiber reinforced plastic and the cellulose nanofiber in separate layers is time-consuming and requires the production of separate layers, which increases the work time and costs.
[0007] The present invention has been made to solve the above-mentioned problems, and aims to provide a cellulose nanofiber-dispersed thermoplastic resin reinforced material that is lightweight and has an excellent elastic modulus, simply and at low cost. [Means for solving the problem]
[0008] In view of the above object, the inventors conducted extensive research and found that, unlike conventional methods, by impregnating cellulose nanofibers and a thermoplastic resin into a woven fabric and / or nonwoven fabric, it is possible to easily and inexpensively produce a thermoplastic resin-reinforced material in which cellulose nanofibers are dispersed without forming carbon fiber reinforced plastic and cellulose nanofibers into separate layers, and that the material is lightweight and has a high elastic modulus. Based on this knowledge, the inventors conducted further research and completed the present invention. That is, the present invention includes the following configurations.
[0009] Item 1. A cellulose nanofiber-dispersed thermoplastic resin reinforced material having a cellulose nanofiber-dispersed thermoplastic resin layer in which cellulose nanofibers and thermoplastic resin are impregnated inside a woven fabric and / or nonwoven fabric.
[0010] Item 2. The cellulose nanofiber-dispersed thermoplastic resin reinforced material according to Item 1, wherein the fibers constituting the woven fabric are carbon fibers.
[0011] Item 3. The cellulose nanofiber-dispersed thermoplastic resin reinforced material according to Item 1 or 2, wherein the nonwoven fabric is a carbon nonwoven fabric.
[0012] Item 4. The cellulose nanofiber-dispersed thermoplastic resin reinforced material according to any one of Items 1 to 3, wherein the thermoplastic resin is at least one selected from the group consisting of urethane resin, polyolefin resin, polyester resin, polyamide resin, polystyrene resin, vinyl resin, polyvinyl alcohol resin, polycarbonate resin, polyacetal resin, ethylene-vinyl acetate copolymer resin, and acrylonitrile-butadiene-styrene copolymer resin.
[0013] Item 5. The cellulose nanofiber-dispersed thermoplastic resin reinforced material according to any one of Items 1 to 4, further comprising a carbon fiber reinforced plastic layer on at least one side of the cellulose nanofiber-dispersed thermoplastic resin layer.
[0014] Item 6. A method for producing a cellulose nanofiber-dispersed thermoplastic resin reinforced material according to any one of items 1 to 5, (1A) a step of immersing the woven fabric and / or nonwoven fabric in a dispersion of the cellulose nanofibers and the thermoplastic resin; or (1B) A step of immersing the woven fabric and / or nonwoven fabric in a dispersion of the cellulose nanofibers and then impregnating the woven fabric and / or nonwoven fabric with an emulsion of the thermoplastic resin. A manufacturing method comprising:
[0015] Item 7. The method according to Item 6, wherein a roller treatment is performed during the immersion in the dispersion in the step (1A) or during the immersion in the emulsion in the step (1B).
[0016] Item 8. The manufacturing method according to Item 6 or 7, wherein in the step (1A) or (1B), the amount of the cellulose nanofiber added is 0.1 to 100 parts by mass per 100 parts by mass of the woven fabric and / or nonwoven fabric.
[0017] Item 9. The method according to any one of Items 6 to 8, wherein in the step (1A) or (1B), the amount of the thermoplastic resin added is 50 to 900 parts by mass per 100 parts by mass of the woven fabric and / or nonwoven fabric.
[0018] Item 10. After the step (1A) or (1B), (2) A step of heating the cellulose nanofiber-dispersed thermoplastic resin reinforced material obtained in step (1) to remove moisture. The method for producing the same according to any one of items 6 to 9,
[0019] Item 11. After the step (2), (3) A step of heating and molding the obtained cellulose nanofiber-dispersed thermoplastic resin reinforced material under pressure. The manufacturing method according to item 10, comprising:
[0020] Item 12. The method according to item 11, wherein the molding pressure in the step (3) is 5 MPa or more. Effect of the Invention
[0021] According to the present invention, a cellulose nanofiber-dispersed thermoplastic resin reinforced material can be provided that is lightweight and has an excellent elastic modulus, easily and at low cost, without the need for hydrophobic treatment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] In this specification, the term "containing" is a concept that encompasses all of "comprise," "consist essentially of," and "consist only of."
[0023] In this specification, when a numerical range is indicated as "A to B," it means A or more and B or less.
[0024] 1. Cellulose nanofiber-dispersed thermoplastic resin reinforced material The cellulose nanofiber-dispersed thermoplastic resin reinforced material of the present invention has a cellulose nanofiber-dispersed thermoplastic resin layer in which woven fabric and / or nonwoven fabric are impregnated with cellulose nanofibers and thermoplastic resin.
[0025] According to such a configuration, the presence of the thermoplastic resin allows the cellulose nanofibers to efficiently impregnate the interior of the woven fabric and / or nonwoven fabric, and the elastic modulus can also be improved by capillary action. A thermoplastic resin reinforced material in which the cellulose nanofibers are dispersed can be produced, which is lightweight and has a high elastic modulus. Conversely, this makes it possible to reduce the amount of carbon fiber reinforced plastic that was previously required for the required elastic modulus, which can also lead to resource conservation. Furthermore, since cellulose nanofibers are lighter than carbon fiber reinforced plastics, this can also lead to lighter products.
[0026] (1-1) Cellulose nanofiber-dispersed thermoplastic resin layer Woven and / or nonwoven fabrics The fibers constituting the woven fabric are not particularly limited, and a wide variety of organic fibers can be used, including inorganic fibers such as carbon fibers (PAN-based carbon fibers, pitch-based carbon fibers, carbon nanotubes, etc.), glass fibers (glass wool, glass fibers, etc.), mineral fibers (chrysotile asbestos, white asbestos, blue asbestos, brown asbestos, rectilinear asbestos, tremolite asbestos, and positive asbestos, etc.), artificial mineral fibers (rock wool, ceramic fibers, etc.), and metal fibers (stainless steel fibers, aluminum fibers, iron fibers, nickel fibers, and copper fibers, etc.); synthetic fibers (nylon fibers, polyester fibers, acrylic fibers, vinylon fibers, polyolefin fibers, polyethylene fibers, polypropylene fibers, and polyurethane fibers, etc.), regenerated fibers (rayon, polynosic, cupra, lyocell, acetate, etc.), plant fibers (cotton fibers, hemp fibers, flax fibers, etc.), and animal fibers (wool, silk, wild silk, mohair, cashmere, camel, llama, alpaca, vicuna, angora, and spider silk, etc.). These fibers may be used alone or in combination of two or more kinds. Among them, carbon fiber fabrics are preferred from the viewpoints of light weight, elastic modulus, etc.
[0027] The form of the fibers may be any of continuous long fibers, short fibers obtained by cutting continuous long fibers, milled yarn obtained by pulverizing into a powder, and the like.
[0028] The thickness of the woven fabric is not particularly limited and may vary depending on the type of fiber, but may be, for example, 50 μm to 30 mm, and preferably 100 μm to 10 mm, from the viewpoints of light weight, elasticity, etc.
[0029] The basis weight of the woven fabric is not particularly limited, but is, for example, 5 to 300 g / m from the viewpoints of light weight, elasticity, etc. 2 , preferably 10 to 200 g / m 2 It can be said that:
[0030] The filament diameter of the fibers constituting the weaving yarn in the woven fabric is not particularly limited, but from the viewpoints of light weight, elastic modulus, etc., it can be, for example, 5 to 20 μm, preferably 5 to 10 μm.
[0031] The weaving yarns constituting the woven fabric may be fiber bundles. From the viewpoints of light weight, elasticity, etc., the fiber bundles preferably consist of, for example, 500 to 8000 filaments (original yarns), and more preferably 1000 to 6000 filaments (original yarns).
[0032] The fibers may be coated with known finishing agents such as flame retardants, water absorbents, water repellents, softeners, heat storage agents, ultraviolet ray shielding agents, antistatic agents, antibacterial agents, deodorants, insect repellents, mosquito repellents, phosphorescent agents, retroreflective agents, and bundling agents.
[0033] The fibers constituting the nonwoven fabric are not particularly limited, and a wide variety of organic fibers can be used, including, for example, inorganic fibers such as carbon fibers (PAN-based carbon fibers, pitch-based carbon fibers, carbon nanotubes, etc.), glass fibers (glass wool, glass fibers, etc.), mineral fibers (chrysotile asbestos, white asbestos, blue asbestos, brown asbestos, rectilinear asbestos, tremolite asbestos, and positive asbestos, etc.), artificial mineral fibers (rock wool, ceramic fibers, etc.), and metal fibers (stainless steel fibers, aluminum fibers, iron fibers, nickel fibers, and copper fibers, etc.); synthetic fibers (nylon fibers, polyester fibers, acrylic fibers, vinylon fibers, polyolefin fibers, polyethylene fibers, polypropylene fibers, and polyurethane fibers, etc.), regenerated fibers (rayon, polynosic, cupra, lyocell, acetate, etc.), plant fibers (cotton fibers, hemp fibers, flax fibers, etc.), and animal fibers (wool, silk, wild silk, mohair, cashmere, camel, llama, alpaca, vicuna, angora, and spider silk, etc.). These fibers can be used alone or in combination of two or more. Among them, carbon nonwoven fabrics using carbon fibers are preferred from the viewpoints of light weight, elastic modulus, etc.
[0034] The form of the fibers may be any of continuous long fibers, short fibers obtained by cutting continuous long fibers, milled yarn obtained by pulverizing into a powder, and the like.
[0035] The thickness of the nonwoven fabric is not particularly limited and may vary depending on the type of fiber. From the viewpoints of light weight, elasticity, etc., the thickness of the nonwoven fabric may be, for example, 50 μm to 30 mm, and preferably 100 μm to 10 mm.
[0036] The basis weight of the nonwoven fabric is not particularly limited, but is, for example, 10 to 500 g / m from the viewpoints of light weight, elasticity, etc. 2 , preferably 20 to 200 g / m 2 It can be said that:
[0037] The fibers may be coated with known finishing agents such as flame retardants, water absorbents, water repellents, softeners, heat storage agents, ultraviolet ray shielding agents, antistatic agents, antibacterial agents, deodorants, insect repellents, mosquito repellents, phosphorescent agents, retroreflective agents, and bundling agents.
[0038] Cellulose Nanofiber The cellulose nanofibers may be any known type and are not particularly limited. The cellulose constituting the cellulose nanofibers may be any of plant-derived cellulose, animal-derived cellulose, and bacterial-derived cellulose. These may be used alone or in combination of two or more types.
[0039] The plant-derived cellulose can be selected from, for example, cellulose derived from broad-leaved trees (eucalyptus, poplar, etc.), cellulose derived from conifers (pine, fir, cedar, cypress, etc.), cellulose derived from herbaceous plants (straw, bagasse, reed, kenaf, abaca, sisal, etc.), and seed hair fibers (cotton, etc.). The raw pulp may be mechanical pulp obtained by mechanically treating wood chips, chemical pulp obtained by chemically removing non-cellulose components from wood chips, or dissolving pulp obtained by further removing non-cellulose components and refining.
[0040] Other examples include cellulose derived from animals such as sea squirts, and cellulose derived from bacteria such as nata de coco. Such cellulose does not necessarily have to be composed of pure cellulose components, and non-cellulose components may be associated with the main component cellulose. Of course, it may be composed of only pure cellulose components.
[0041] The main non-cellulose components associated with the cellulose nanofibers are not particularly limited and can be appropriately selected depending on the application. Examples include hemicellulose and lignin.
[0042] The ratio of pure cellulose components in the cellulose nanofibers may also be appropriately set depending on the application. For example, the ratio of pure cellulose components is preferably 70% by mass or more, and more preferably 80% by mass or more, in 100% by mass of the cellulose nanofibers. The upper limit of the ratio of pure cellulose components may be 100% by mass. In this specification, the cellulose ratio refers to the ratio of pure cellulose components in which β-glucose molecules are linearly polymerized through glycosidic bonds, relative to 100% by mass of the entire cellulose nanofiber.
[0043] The degree of polymerization of the pure cellulose component contained in the cellulose nanofiber can also be set appropriately depending on the application. For example, a cellulose component with a degree of polymerization of 500 or more, particularly 600 or more, can be used. There is no particular upper limit to the degree of polymerization of the cellulose component, but it can be set to, for example, 100,000.
[0044] There is no particular restriction on the crystallinity of the pure cellulose component contained in the cellulose nanofiber, and it is preferably 60% or more, and more preferably 70% or more. There is no particular restriction on the upper limit of the crystallinity of cellulose, but it can be, for example, 99%. The crystal structure of the cellulose component can be type I, type II, type III, or type IV.
[0045] There are no particular limitations on the size of the cellulose nanofibers, and when employing the production method of the present invention described below, the diameter is preferably 3 to 500 nm and the length is preferably 100 nm or more from the viewpoints of dispersibility, light weight, elastic modulus, etc. In this specification, the diameter of the cellulose nanofibers is the median diameter obtained by SEM observation of 50 or more randomly selected cellulose nanofibers.
[0046] thermoplastic resin The thermoplastic resin is not particularly limited, and examples thereof include urethane resin, polyolefin resin (polyethylene resin, polypropylene resin, etc.), polyester resin, polyamide resin, polystyrene resin, vinyl resin (polyvinyl chloride resin, polyvinyl acetate resin, polyvinylidene chloride resin, etc.), polyvinyl alcohol resin, polycarbonate resin, polyacetal resin, ethylene vinyl acetate copolymer resin, acrylonitrile butadiene styrene copolymer resin (ABS resin), etc. These thermoplastic resins can be used alone or in combination of two or more. As these thermoplastic resins, urethane resin, polyolefin resin, polyester resin, polyamide resin, etc. are preferred from the viewpoints of ease of impregnation into woven fabrics and / or nonwoven fabrics, light weight, elastic modulus, etc., and urethane resin is more preferred.
[0047] Cellulose nanofiber dispersed thermoplastic resin layer As described above, the cellulose nanofiber-dispersed thermoplastic resin layer is impregnated with cellulose nanofibers and a thermoplastic resin inside the woven fabric and / or nonwoven fabric. Unlike the conventional method, the cellulose nanofiber layer is not formed separately from the carbon fiber reinforced plastic layer, but the cellulose nanofibers and the thermoplastic resin are impregnated inside the woven fabric and / or nonwoven fabric. In other words, conventionally, reinforcement was performed by providing a clear cellulose nanofiber layer, but in the present invention, a cellulose nanofiber-dispersed thermoplastic resin-reinforced material that is lightweight and has excellent elasticity can be obtained without providing a clear cellulose nanofiber layer by permeating the woven fabric and / or nonwoven fabric with the cellulose nanofiber-dispersed thermoplastic resin. Therefore, it is possible to eliminate the clear interface with the CFRP layer that occurs when a clear cellulose nanofiber layer is provided, and the strength is improved.
[0048] According to the manufacturing method described below, the cellulose nanofiber-dispersed thermoplastic resin reinforced material of the present invention is produced by immersing a woven fabric and / or nonwoven fabric in a dispersion of cellulose nanofibers and the thermoplastic resin, or by immersing a woven fabric and / or nonwoven fabric in a dispersion of cellulose nanofibers and then impregnating the woven fabric and / or nonwoven fabric with an emulsion of a thermoplastic resin, so that it is difficult to strictly specify the contents of various components in the cellulose nanofiber-dispersed thermoplastic resin layer. However, from the viewpoints of light weight, elastic modulus, etc., the content of cellulose nanofiber is preferably 0.1 to 100 parts by mass, more preferably 0.5 to 20 parts by mass, per 100 parts by mass of the woven fabric and / or nonwoven fabric.
[0049] According to the manufacturing method of the cellulose nanofiber-dispersed thermoplastic resin reinforced material of the present invention described below, a woven fabric and / or nonwoven fabric is immersed in a dispersion of cellulose nanofibers and the thermoplastic resin, or the woven fabric and / or nonwoven fabric is immersed in a dispersion of cellulose nanofibers and then impregnated with an emulsion of a thermoplastic resin, so it is difficult to strictly specify the contents of various components in the cellulose nanofiber-dispersed thermoplastic resin layer. However, from the viewpoints of light weight, elastic modulus, etc., the content of the thermoplastic resin is preferably 50 to 900 parts by mass, more preferably 100 to 300 parts by mass, per 100 parts by mass of the woven fabric and / or nonwoven fabric.
[0050] (1-2) Carbon fiber reinforced plastic layer The cellulose nanofiber-dispersed thermoplastic resin reinforced material of the present invention may be composed only of the cellulose nanofiber-dispersed thermoplastic resin layer, but it may also be provided with a carbon fiber reinforced plastic layer on at least one side of the cellulose nanofiber-dispersed thermoplastic resin layer. In the present invention, the carbon fiber reinforced plastic layer is a layer containing carbon fiber reinforced plastic.
[0051] This carbon fiber reinforced plastic can usually employ a layer in which carbon fibers are impregnated with a thermoplastic resin, that is, the carbon fibers are dispersed in a thermoplastic resin matrix.
[0052] In this case, the carbon fiber material is not particularly limited as long as it is a structure made of carbon fibers (particularly a structure made of conductive carbon fibers). Examples include a planar carbon fiber sheet, a pipe-shaped carbon fiber sheet, a wing-shaped carbon fiber sheet, an L-shaped carbon fiber sheet, and an H-shaped carbon fiber sheet. In particular, not only carbon fiber materials in which carbon fibers are arranged in a straight line, but also carbon fiber materials with complex three-dimensional shapes can be used. The fiber diameter of each carbon fiber constituting such a carbon fiber material is preferably 0.001 to 50 μm on average from the viewpoints of light weight, elastic modulus, etc. As such a carbon fiber material, a publicly known or commercially available product can be used.
[0053] The thermoplastic resin is not particularly limited, and examples thereof include urethane resin, polyolefin resin (polyethylene resin, polypropylene resin, etc.), polyester resin, polyamide resin, polystyrene resin, vinyl resin (polyvinyl chloride resin, polyvinyl acetate resin, polyvinylidene chloride resin, etc.), polyvinyl alcohol resin, polycarbonate resin, polyacetal resin, ethylene vinyl acetate copolymer resin, acrylonitrile butadiene styrene copolymer resin (ABS resin), etc. These thermoplastic resins can be used alone or in combination of two or more. As these thermoplastic resins, from the viewpoints of light weight, elastic modulus, etc., urethane resin, polyolefin resin, polyester resin, polyamide resin, etc. are preferred, and urethane resin is more preferred.
[0054] The thickness of such a carbon fiber reinforced plastic layer is preferably 10 to 500 μm, and more preferably 50 to 200 μm, from the viewpoints of light weight, elastic modulus, and the like.
[0055] Since the carbon fiber reinforced plastic layer is a layer in which carbon fibers are impregnated with a thermoplastic resin, it is difficult to strictly specify the contents of various components. However, from the viewpoints of light weight, elastic modulus, etc., the content of the thermoplastic resin is preferably 50 to 900 parts by mass, more preferably 100 to 300 parts by mass, per 100 parts by mass of carbon fibers.
[0056] (1-3) Cellulose nanofiber-dispersed thermoplastic resin reinforced material As described above, the cellulose nanofiber-dispersed thermoplastic resin reinforced material of the present invention has at least a cellulose nanofiber-dispersed thermoplastic resin layer, and can also have a carbon fiber reinforced plastic layer as necessary.
[0057] The configuration of such a cellulose nanofiber-dispersed thermoplastic resin reinforced material of the present invention is not particularly limited as long as it has a cellulose nanofiber-dispersed thermoplastic resin layer, and it is also possible to adopt a configuration in which at least one cellulose nanofiber-dispersed thermoplastic resin layer is arranged between two carbon fiber reinforced plastic layers, or a configuration in which carbon fiber reinforced plastic layers and cellulose nanofiber-dispersed thermoplastic resin layers are arranged alternately.
[0058] According to the present invention, a cellulose nanofiber-dispersed thermoplastic resin reinforced material that is lightweight and has excellent elasticity can be obtained, making it possible to manufacture lightweight sports goods that could not be achieved by conventional techniques. Specifically, it is expected to be put to practical use in golf clubs (whole), tennis rackets (frames, shafts, etc.), baseball and softball bats (whole), badminton rackets (frames, shafts, etc.), shoes (soles and built-in plates), etc.
[0059] For example, baseball and softball bats have thick carbon fiber layers to improve durability because the surface and carbon fiber layers break when the bat is repeatedly struck with a ball. According to the present invention, a cellulose nanofiber-dispersed thermoplastic resin reinforced material with excellent elastic modulus can be obtained, making it possible to reduce the number of carbon fiber layers and reduce the weight.
[0060] In addition, although a badminton racket or the like does not break in the frame or shaft simply by hitting a shuttlecock, it is common for items other than the shuttlecock to be hit by mistake, and so it is necessary to ensure the elastic modulus of the product. In addition, high-elasticity carbon fibers are sometimes used to reduce the weight of the shaft, but in that case the elastic modulus tends to be low, so the carbon fiber layer is made thicker to increase durability. According to the present invention, a cellulose nanofiber-dispersed thermoplastic resin reinforced material with excellent elastic modulus can be obtained, making it possible to reduce the number of carbon fiber layers and reduce weight.
[0061] Carbon fiber reinforced plastic materials, which have been popular in the sports market, are often used in aerospace and industrial applications. Therefore, in addition to the above-mentioned applications in sporting goods, they can also be used in the bodies and parts of automobiles and aircraft, which are currently being made lighter, and in ETC gate bars on highways.
[0062] Furthermore, in Japan, where the aging society is accelerating, maintaining the health of the elderly is a major issue. The elderly gradually lose their physical strength and muscle power, leading to a situation where it becomes increasingly difficult to move around. For clothing, shoes, braces, etc. that support the walking of the elderly, the use of the cellulose nanofiber-dispersed thermoplastic resin reinforced material of the present invention makes it possible to develop lightweight and durable products, which are also useful for products for the elderly.
[0063] 2. Manufacturing method for cellulose nanofiber-dispersed thermoplastic resin reinforced material The method for producing the cellulose nanofiber-dispersed thermoplastic resin reinforced material of the present invention is not particularly limited, but may be (1A) a step of immersing the woven fabric and / or nonwoven fabric in a dispersion of the cellulose nanofibers and the thermoplastic resin; or (1B) A step of immersing the woven fabric and / or nonwoven fabric in a dispersion of the cellulose nanofibers and then impregnating the woven fabric and / or nonwoven fabric with an emulsion of the thermoplastic resin. Equipped with.
[0064] By adopting such a method, even if the cellulose nanofibers are not subjected to a hydrophobic treatment in step (1A) or (1B), the presence of the thermoplastic resin makes it possible for the cellulose nanofibers to efficiently impregnate the inside of the woven fabric and / or nonwoven fabric, and also makes it possible to improve the elastic modulus through capillary action.
[0065] Furthermore, by adopting such a method, it is possible to improve the elastic modulus by using cellulose nanofibers. This, in turn, makes it possible to reduce the amount of carbon fiber reinforced plastic that was previously required to achieve the desired elastic modulus, which may lead to resource conservation. Furthermore, since cellulose nanofibers are lighter than carbon fiber reinforced plastics, this may lead to weight reduction in products, and in particular to improved fuel efficiency in the case of moving objects (automobiles, aircraft, etc.).
[0066] (2-1) Process (1A) The cellulose nanofibers, thermoplastic resin, and woven fabric and / or nonwoven fabric may be those described in the above "(1-1) Cellulose nanofiber-dispersed thermoplastic resin layer." The same applies to preferred aspects. Note that microgel may also be used as the thermoplastic resin.
[0067] The dispersion of cellulose nanofibers and thermoplastic resin further contains a solvent (such as monoalcohols such as methanol, ethanol, propanol, isopropanol, and butanol, Examples of polyhydric alcohols include ethylene diols such as ethylene glycol, diethylene glycol, thiodiethylene glycol, triethylene glycol, tetraethylene glycol, and polyethylene glycol; propane diols such as 2-methyl-1,3-propanediol, 2-ethyl-1,3-propanediol, and 3-methoxy-1,2-propanediol; butane diols such as 2-butene-1,4-diol, 1,3-butanediol, and 2-methyl-1,4-butanediol; 2-methyl-2,4-pentanediol, 1,5-pentanediol, 1,4-pentanediol, and 3-methyl-1,3-pentanediol; pentanediol, 2,4-diethyl-1,5-pentanediol, and other pentanediols; hexanediols, such as 1,2-hexanediol; heptanediols, such as 1,2,6-trimethyl-1,7-heptanediol, 2,4,6-triethyl-1,7-heptanediol; octanediols, such as 3,6-dithia-1,8-octanediol; alkylene diols, such as propylene glycol, dipropylene glycol, polypropylene glycol, butylene glycol; polyols, such as glycerin, hexanetriol, thiodiglycol, trimethylolpropane; acetylene alcohol, and the like. Examples of glycol derivatives include ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monomethyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monobutyl ether, dipropylene glycol monomethyl ether, triethylene glycol monomethyl ether, polyethylene glycol monomethyl ether, ethylene glycol monoisopropyl ether, triethylene glycol monobutyl ether, ethylene glycol monoisobutyl ether, diethylene glycol monoisobutyl ether, propylene glycol monopropyl ether, ethylene glycol diacetate, ethylene glycol monomethyl ether acetate, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, and ethylene glycol monophenyl ether. Examples of amines include ethanolamine, diethanolamine, triethanolamine, N-methyldiethanolamine, N-ethyldiethanolamine, morpholine, N-ethylmorpholine, ethylenediamine, diethylenetriamine, triethylenetetramine, polyethyleneimine, and tetramethylpropylenediamine. Other polar solvents include, for example, formamide, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, sulfolane, 3-methylsulfolane, 3-sulfolene, bis(2-hydroxyethyl)sulfone, 2-pyrrolidone, N-methyl-2-pyrrolidone, N-vinyl-2-pyrrolidone, 2-pyrrolidone-5-carboxylic acid, 2-oxazolidone, 1,3-dimethyl-2-imidazolidinone, acetonitrile, acetone, diacetone alcohol, 4-picoline, etc., as well as pigments (carbon, titanium oxide, lead silicate, aluminum phosphate, bismuth hydroxide, yttrium hydroxide, aluminum silicate, talc, etc.), functional agents (microgel, etc.), acids (acetic acid, lactic acid, formic acid, propionic acid, sulfamic acid, etc.), etc.
[0068] In this way, by immersing a woven fabric and / or nonwoven fabric in a dispersion of cellulose nanofibers and a thermoplastic resin, the inside of the woven fabric and / or nonwoven fabric can be impregnated with the cellulose nanofibers and the thermoplastic resin.
[0069] The amount (charge amount) of each component used in this case is not particularly limited, but the amount (charge amount) of the cellulose nanofiber and the thermoplastic resin used can be adjusted to be within the above-mentioned content range. However, according to the production method of the present invention, it is also possible to assume that when the woven fabric and / or nonwoven fabric is immersed in a dispersion of the cellulose nanofiber and the thermoplastic resin, only a part of the cellulose nanofiber and the thermoplastic resin is impregnated into the inside of the woven fabric and / or nonwoven fabric, and the amount (charge amount) of the cellulose nanofiber and the thermoplastic resin used can be greater than the above-mentioned content. For this reason, the amount (charge amount) of the cellulose nanofiber used is preferably 0.1 to 100 parts by mass, more preferably 0.5 to 20 parts by mass, per 100 parts by mass of the woven fabric and / or nonwoven fabric. The amount (charge amount) of the thermoplastic resin used is preferably 50 to 900 parts by mass, more preferably 100 to 300 parts by mass, per 100 parts by mass of the woven fabric and / or nonwoven fabric.
[0070] In the manufacturing method of the present invention, in the dispersion of cellulose nanofibers and thermoplastic resin, it is believed that the thermoplastic resin (particularly the microgel of the thermoplastic resin) penetrates into the network structure (=mesh-like) of the cellulose nanofibers, and is uniformly dispersed in combination with the action of the polymer functional groups. When a woven fabric and / or nonwoven fabric is immersed in the dispersion in this state, the cellulose nanofibers can be impregnated into the interior of the woven fabric and / or nonwoven fabric together with the thermoplastic resin that has penetrated into the network structure.
[0071] In the manufacturing method of the present invention, the temperature when immersing the woven fabric and / or nonwoven fabric in the dispersion of cellulose nanofibers and thermoplastic resin is not limited, but from the viewpoint of easily impregnating the cellulose nanofibers and thermoplastic resin into the interior of the woven fabric and / or nonwoven fabric, a temperature of 10 to 90°C is preferred, and 20 to 70°C is more preferred.
[0072] In the manufacturing method of the present invention, the time for which the woven fabric and / or nonwoven fabric is immersed in the dispersion of cellulose nanofibers and thermoplastic resin is not limited, but from the viewpoint of easily impregnating the cellulose nanofibers and thermoplastic resin into the interior of the woven fabric and / or nonwoven fabric, the time is preferably 0.5 to 48 hours, and more preferably 2 to 6 hours.
[0073] As described above, after carrying out step (1A), it is also possible to carry out a roller treatment. By carrying out the roller treatment, the gaps between the cellulose nanofibers and the thermoplastic resin can be reduced, and the cellulose nanofibers and the thermoplastic resin can be easily impregnated further into the woven fabric and / or nonwoven fabric.
[0074] The roller treatment is not particularly limited, but can be carried out according to a conventional method.
[0075] In the method of the present invention for producing a cellulose nanofiber-dispersed thermoplastic resin reinforced material, the above step (1A) can be repeated multiple times (particularly 2 to 3 times), which makes it easier to further impregnate the cellulose nanofibers and thermoplastic resin into the woven fabric and / or nonwoven fabric.
[0076] (2-2) Process (1B) The cellulose nanofibers, thermoplastic resin, and woven fabric and / or nonwoven fabric may be those described in the above "(1-1) Cellulose nanofiber-dispersed thermoplastic resin layer." The same applies to preferred aspects. Note that microgel may also be used as the thermoplastic resin.
[0077] The cellulose nanofiber dispersion liquid further contains a solvent (such as monoalcohols such as methanol, ethanol, propanol, isopropanol, and butanol, Examples of polyhydric alcohols include ethylene diols such as ethylene glycol, diethylene glycol, thiodiethylene glycol, triethylene glycol, tetraethylene glycol, and polyethylene glycol; propane diols such as 2-methyl-1,3-propanediol, 2-ethyl-1,3-propanediol, and 3-methoxy-1,2-propanediol; butane diols such as 2-butene-1,4-diol, 1,3-butanediol, and 2-methyl-1,4-butanediol; 2-methyl-2,4-pentanediol, 1,5-pentanediol, 1,4-pentanediol, and 3-methyl-1,3-pentanediol; pentanediol, 2,4-diethyl-1,5-pentanediol, and other pentanediols; hexanediols, such as 1,2-hexanediol; heptanediols, such as 1,2,6-trimethyl-1,7-heptanediol, 2,4,6-triethyl-1,7-heptanediol; octanediols, such as 3,6-dithia-1,8-octanediol; alkylene diols, such as propylene glycol, dipropylene glycol, polypropylene glycol, butylene glycol; polyols, such as glycerin, hexanetriol, thiodiglycol, trimethylolpropane; acetylene alcohol, and the like. Examples of glycol derivatives include ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monomethyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monobutyl ether, dipropylene glycol monomethyl ether, triethylene glycol monomethyl ether, polyethylene glycol monomethyl ether, ethylene glycol monoisopropyl ether, triethylene glycol monobutyl ether, ethylene glycol monoisobutyl ether, diethylene glycol monoisobutyl ether, propylene glycol monopropyl ether, ethylene glycol diacetate, ethylene glycol monomethyl ether acetate, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, and ethylene glycol monophenyl ether. Examples of amines include ethanolamine, diethanolamine, triethanolamine, N-methyldiethanolamine, N-ethyldiethanolamine, morpholine, N-ethylmorpholine, ethylenediamine, diethylenetriamine, triethylenetetramine, polyethyleneimine, and tetramethylpropylenediamine. Other polar solvents include, for example, formamide, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, sulfolane, 3-methylsulfolane, 3-sulfolene, bis(2-hydroxyethyl)sulfone, 2-pyrrolidone, N-methyl-2-pyrrolidone, N-vinyl-2-pyrrolidone, 2-pyrrolidone-5-carboxylic acid, 2-oxazolidone, 1,3-dimethyl-2-imidazolidinone, acetonitrile, acetone, diacetone alcohol, 4-picoline, etc., as well as pigments (carbon, titanium oxide, lead silicate, aluminum phosphate, bismuth hydroxide, yttrium hydroxide, aluminum silicate, talc, etc.), functional agents (microgel, etc.), acids (acetic acid, lactic acid, formic acid, propionic acid, sulfamic acid, etc.), etc.
[0078] The thermoplastic resin emulsion further contains a solvent (such as alcohols, for example, monoalcohols such as methanol, ethanol, propanol, isopropanol, and butanol, Examples of polyhydric alcohols include ethylene diols such as ethylene glycol, diethylene glycol, thiodiethylene glycol, triethylene glycol, tetraethylene glycol, and polyethylene glycol; propane diols such as 2-methyl-1,3-propanediol, 2-ethyl-1,3-propanediol, and 3-methoxy-1,2-propanediol; butane diols such as 2-butene-1,4-diol, 1,3-butanediol, and 2-methyl-1,4-butanediol; 2-methyl-2,4-pentanediol, 1,5-pentanediol, 1,4-pentanediol, and 3-methyl-1,3-pentanediol; pentanediol, 2,4-diethyl-1,5-pentanediol, and other pentanediols; hexanediols, such as 1,2-hexanediol; heptanediols, such as 1,2,6-trimethyl-1,7-heptanediol, 2,4,6-triethyl-1,7-heptanediol; octanediols, such as 3,6-dithia-1,8-octanediol; alkylene diols, such as propylene glycol, dipropylene glycol, polypropylene glycol, butylene glycol; polyols, such as glycerin, hexanetriol, thiodiglycol, trimethylolpropane; acetylene alcohol, and the like. Examples of glycol derivatives include ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monomethyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monobutyl ether, dipropylene glycol monomethyl ether, triethylene glycol monomethyl ether, polyethylene glycol monomethyl ether, ethylene glycol monoisopropyl ether, triethylene glycol monobutyl ether, ethylene glycol monoisobutyl ether, diethylene glycol monoisobutyl ether, propylene glycol monopropyl ether, ethylene glycol diacetate, ethylene glycol monomethyl ether acetate, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, and ethylene glycol monophenyl ether. Examples of amines include ethanolamine, diethanolamine, triethanolamine, N-methyldiethanolamine, N-ethyldiethanolamine, morpholine, N-ethylmorpholine, ethylenediamine, diethylenetriamine, triethylenetetramine, polyethyleneimine, and tetramethylpropylenediamine. Other polar solvents include, for example, formamide, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, sulfolane, 3-methylsulfolane, 3-sulfolene, bis(2-hydroxyethyl)sulfone, 2-pyrrolidone, N-methyl-2-pyrrolidone, N-vinyl-2-pyrrolidone, 2-pyrrolidone-5-carboxylic acid, 2-oxazolidone, 1,3-dimethyl-2-imidazolidinone, acetonitrile, acetone, diacetone alcohol, 4-picoline, etc., as well as pigments (carbon, titanium oxide, lead silicate, aluminum phosphate, bismuth hydroxide, yttrium hydroxide, aluminum silicate, talc, etc.), functional agents (microgel, etc.), acids (acetic acid, lactic acid, formic acid, propionic acid, sulfamic acid, etc.), etc.
[0079] In this way, by immersing a woven fabric and / or nonwoven fabric in a dispersion of cellulose nanofibers and then immersing the woven fabric and / or nonwoven fabric after immersion in the dispersion of cellulose nanofibers in an emulsion of thermoplastic resin, the interior of the woven fabric and / or nonwoven fabric can be impregnated with the cellulose nanofibers and thermoplastic resin.
[0080] The amount (charge amount) of each component used in this case is not particularly limited, but the amount (charge amount) of the cellulose nanofiber and the thermoplastic resin used can be adjusted to be within the above-mentioned content range. However, according to the production method of the present invention, it is also possible to assume a case where only a part of the cellulose nanofiber is impregnated into the inside of the woven fabric and / or nonwoven fabric when the woven fabric and / or nonwoven fabric is immersed in a dispersion of cellulose nanofiber, or a case where only a part of the thermoplastic resin is impregnated into the inside of the woven fabric and / or nonwoven fabric when the woven fabric and / or nonwoven fabric after immersion in a dispersion of cellulose nanofiber is immersed in an emulsion of a thermoplastic resin, and the amount (charge amount) of the cellulose nanofiber and the thermoplastic resin used can be greater than the above-mentioned content. For this reason, the amount (charge amount) of the cellulose nanofiber used is preferably 0.1 to 100 parts by mass, more preferably 0.5 to 20 parts by mass, per 100 parts by mass of the woven fabric and / or nonwoven fabric. The amount of the thermoplastic resin used (charged amount) is preferably 50 to 900 parts by mass, and more preferably 100 to 300 parts by mass, per 100 parts by mass of the woven fabric and / or nonwoven fabric.
[0081] In the manufacturing method of the present invention, a woven fabric and / or nonwoven fabric is immersed in a dispersion of cellulose nanofibers, and then the woven fabric and / or nonwoven fabric after immersion in the dispersion of cellulose nanofibers is immersed in an emulsion of thermoplastic resin.The thermoplastic resin (particularly a thermoplastic resin microgel) penetrates into the network structure (=mesh-like) of the cellulose nanofibers, and in combination with the action of the polymer functional groups, the cellulose nanofibers are uniformly dispersed, and the cellulose nanofibers can be impregnated into the interior of the woven fabric and / or nonwoven fabric together with the thermoplastic resin that has penetrated into the network structure.
[0082] In the manufacturing method of the present invention, the temperature when immersing the woven fabric and / or nonwoven fabric in the dispersion of cellulose nanofibers and the emulsion of thermoplastic resin is not limited, but from the viewpoint of easily impregnating the cellulose nanofibers and thermoplastic resin into the interior of the woven fabric and / or nonwoven fabric, a temperature of 10 to 90°C is preferred, and 20 to 70°C is more preferred.
[0083] In the manufacturing method of the present invention, the time for which the woven fabric and / or nonwoven fabric is immersed in the dispersion of cellulose nanofibers and the emulsion of thermoplastic resin is not limited, but from the viewpoint of easily impregnating the cellulose nanofibers and thermoplastic resin into the interior of the woven fabric and / or nonwoven fabric, the time is preferably 0.5 to 48 hours, and more preferably 2 to 6 hours.
[0084] As described above, after carrying out step (1A), it is also possible to carry out a roller treatment. By carrying out the roller treatment, the gaps between the cellulose nanofibers and the thermoplastic resin can be reduced, and the cellulose nanofibers and the thermoplastic resin can be easily impregnated further into the woven fabric and / or nonwoven fabric.
[0085] The roller treatment is not particularly limited, but can be carried out according to a conventional method.
[0086] In the method of the present invention for producing a cellulose nanofiber-dispersed thermoplastic resin reinforced material, the above step (1A) can be repeated multiple times (particularly 2 to 3 times), which makes it easier to further impregnate the cellulose nanofibers and thermoplastic resin into the woven fabric and / or nonwoven fabric.
[0087] (2-3) Process (2) In the method for producing a cellulose nanofiber-dispersed thermoplastic resin reinforced material of the present invention, after the above-mentioned step (1A) or (1B), (2) A step of heating the cellulose nanofiber-dispersed thermoplastic resin reinforced material obtained in step (1) to remove moisture. It can also be provided with:
[0088] This makes it possible to remove excess water present in the cellulose nanofiber-dispersed thermoplastic resin reinforced material of the present invention.
[0089] In the manufacturing method of the present invention, the temperature at which the cellulose nanofiber-dispersed thermoplastic resin reinforced material is heated to remove moisture is not limited, but from the standpoints of light weight, elastic modulus, etc., a temperature of 10 to 90°C is preferred, and 20 to 70°C is more preferred.
[0090] In the manufacturing method of the present invention, the time for heating the cellulose nanofiber-dispersed thermoplastic resin reinforced material to remove moisture is not limited, but from the standpoints of light weight, elastic modulus, etc., 0.5 to 48 hours is preferable, and 2 to 6 hours is more preferable.
[0091] (2-4) Process (3) In the method for producing a cellulose nanofiber-dispersed thermoplastic resin reinforced material of the present invention, after the above step (2), (3) A step of heating and molding the obtained cellulose nanofiber-dispersed thermoplastic resin reinforced material under pressure. It can also be provided with:
[0092] By performing pressure molding, the gaps between the cellulose nanofibers and the thermoplastic resin can be further reduced.
[0093] In the manufacturing method of the present invention, the temperature at which the cellulose nanofiber-dispersed thermoplastic resin reinforced material is heated and molded is not limited, but from the standpoints of light weight, elastic modulus, etc., a temperature of 10 to 90°C is preferable, and 20 to 70°C is more preferable.
[0094] In the manufacturing method of the present invention, the temperature at which the cellulose nanofiber-dispersed thermoplastic resin reinforced material is heated and molded is not limited, but from the standpoint of light weight, elastic modulus, etc., 0.5 to 48 hours is preferable, and 2 to 6 hours is more preferable.
[0095] In the manufacturing method of the present invention, the pressure when heating and molding the cellulose nanofiber-dispersed thermoplastic resin reinforced material is not limited, but from the standpoint of light weight, elastic modulus, etc., it is preferably 5 MPa or more, more preferably 10 to 60 MPa, and even more preferably 20 to 30 MPa. EXAMPLES
[0096] The present invention will be specifically described based on examples, but the present invention is not limited to these examples.
[0097] In the following Examples and Comparative Examples, the thermoplastic resin used was a water-based thermoplastic resin emulsion, Superflex 130 (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.; thermoplastic urethane resin).
[0098] In the following Examples and Comparative Examples, Rheocrysta I-2SX (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.; average fiber diameter 4 nm, average aspect ratio 280) was used as the cellulose nanofiber.
[0099] [Example 1] Place a sheet of Teflon (registered trademark) on a tray and place a sheet of carbon fiber nonwoven fabric (weight 200g / m2) of approximately the same size on the tray. 2 A mixture of 100 g of Superflex 130 (solid content: 35%), a thermoplastic resin emulsion, and 100 g of Leocrysta I-2SX (cellulose nanofiber content: 0.5%), a cellulose nanofiber dispersion, was placed on the carbon fiber nonwoven fabric, and the fabric was allowed to stand for 30 minutes.
[0100] Next, the carbon fiber nonwoven fabric was left in the tray in a thermostatic chamber at 70° C. for 4 to 6 hours to remove the moisture. In practice, the moisture is removed in about 2 hours.
[0101] The mixture was then heated at 220°C and 24 MPa for 10 minutes and cooled under pressure in a cooling press to form a test piece with a thickness of 1.0 mm. The density of the cellulose nanofiber in the obtained test piece was 1.6 g / cm. 3, the density of thermoplastic resin is 1.0g / cm 3 , the density of carbon fiber is 1.8g / cm 3 It was.
[0102] [Example 2] Place a sheet of Teflon (registered trademark) on a tray and place a sheet of carbon fiber nonwoven fabric (weight 200g / m2) of approximately the same size on the tray. 2 A mixture of 100g of Superflex SF130 (solid content: 35%), a thermoplastic resin emulsion, and 100g of Leocrysta I-2SX (cellulose nanofiber content: 0.5%), a cellulose nanofiber dispersion, was impregnated into the carbon fiber nonwoven fabric, which was then rolled for 2 minutes with a Teflon (registered trademark) roller and allowed to stand for 1 minute. The carbon fiber nonwoven fabric was then turned over and the same operation was carried out again, and the fabric was left for 30 minutes after the roller treatment.
[0103] Next, the carbon fiber nonwoven fabric was left in the tray in a thermostatic chamber at 70° C. for 4 to 6 hours to remove the moisture. In practice, the moisture is removed in about 2 hours.
[0104] The mixture was then heated at 220°C and 24 MPa for 10 minutes and cooled under pressure in a cooling press to form a test piece with a thickness of 1.0 mm. The density of the cellulose nanofiber in the obtained test piece was 1.6 g / cm. 3 , the density of thermoplastic resin is 1.0g / cm 3 , the density of carbon fiber is 1.8g / cm 3 It was.
[0105] [Example 3] Place a sheet of Teflon (registered trademark) on a tray and place a sheet of carbon fiber nonwoven fabric (weight 200g / m2) of approximately the same size on the tray. 2A mixture of 100g of Superflex 130 (solid content: 35%), a thermoplastic resin emulsion, and 100g of Leocrysta I-2SX (cellulose nanofiber content: 0.5%), a cellulose nanofiber dispersion, was impregnated into the carbon fiber nonwoven fabric, which was then rolled for 2 minutes with a Teflon (registered trademark) roller and allowed to stand for 1 minute. The carbon fiber nonwoven fabric was then turned over and the same operation was carried out again, and the fabric was left for 30 minutes after the roller treatment.
[0106] Next, the carbon fiber nonwoven fabric was left in the tray in a thermostatic chamber at 70° C. for 4 to 6 hours to remove the moisture. In practice, the moisture is removed in about 2 hours.
[0107] The mixture was then heated at 220°C and 24 MPa for 5 minutes, and cooled under pressure in a cooling press to form a test piece with a thickness of 1.0 mm. The density of the cellulose nanofiber in the obtained test piece was 1.6 g / cm. 3 , the density of thermoplastic resin is 1.0g / cm 3 , the density of carbon fiber is 1.8g / cm 3 It was.
[0108] [Comparative Example 1] A test piece for Comparative Example 1 was obtained by carrying out the same operation as in Example 1, except that cellulose nanofibers were not used.
[0109] [Comparative Example 2] A test piece for Comparative Example 2 was obtained by carrying out the same operation as in Example 2, except that cellulose nanofibers were not used.
[0110] [Comparative Example 3] A test piece for Comparative Example 3 was obtained by carrying out the same operation as in Example 3, except that cellulose nanofibers were not used.
[0111] Elasticity Modulus The bending test pieces were cut to 15 x 100 mm, and three pieces were prepared for each example. The three-point bending test was performed using a universal material testing machine (59R5582, manufactured by Instron Japan Co., Ltd.), with a constant span of 40 mm and a constant load speed of 2.5 mm / min. Data on the load-deflection relationship was obtained, and the elastic modulus was calculated from the slope of the linear portion.
[0112] As a result, the test piece of Example 3 had an elastic modulus of 28.4 GPa, and the test piece of Comparative Example 3 had an elastic modulus of 22.7 GPa.
Claims
1. A cellulose nanofiber-dispersed thermoplastic resin reinforced material having a cellulose nanofiber-dispersed thermoplastic resin layer impregnated with cellulose nanofibers and a thermoplastic resin inside a woven fabric and / or nonwoven fabric.
2. The cellulose nanofiber-dispersed thermoplastic resin reinforced material according to claim 1 , wherein the fibers constituting the woven fabric are carbon fibers.
3. The cellulose nanofiber-dispersed thermoplastic resin reinforced material according to claim 1 , wherein the nonwoven fabric is a carbon nonwoven fabric.
4. The cellulose nanofiber-dispersed thermoplastic resin reinforced material according to claim 1, wherein the thermoplastic resin is at least one selected from the group consisting of urethane resin, polyolefin resin, polyester resin, polyamide resin, polystyrene resin, vinyl resin, polyvinyl alcohol resin, polycarbonate resin, polyacetal resin, ethylene-vinyl acetate copolymer resin, and acrylonitrile-butadiene-styrene copolymer resin.
5. The cellulose nanofiber-dispersed thermoplastic resin reinforced material according to claim 1 , further comprising a carbon fiber reinforced plastic layer on at least one side of the cellulose nanofiber-dispersed thermoplastic resin layer.
6. A method for producing a cellulose nanofiber-dispersed thermoplastic resin reinforced material according to any one of claims 1 to 5, (1A) a step of immersing the woven fabric and / or nonwoven fabric in a dispersion of the cellulose nanofibers and the thermoplastic resin; or (1B) A step of immersing the woven fabric and / or nonwoven fabric in a dispersion of the cellulose nanofibers and then impregnating the nonwoven fabric with an emulsion of the thermoplastic resin. A manufacturing method comprising:
7. The method according to claim 6 , wherein a roller treatment is performed during the immersion in the dispersion in the step (1A) or the immersion in the emulsion in the step (1B).
8. The method according to claim 6, wherein in step (1A) or (1B), the amount of the cellulose nanofibers added is 0.1 to 100 parts by mass per 100 parts by mass of the woven fabric and / or nonwoven fabric.
9. The method according to claim 6, wherein in the step (1A) or (1B), the amount of the thermoplastic resin added is 5 to 90 parts by mass per 100 parts by mass of the woven fabric and / or nonwoven fabric.
10. After the step (1A) or (1B), (2) A step of heating the cellulose nanofiber-dispersed thermoplastic resin reinforced material obtained in step (1) to remove moisture. The method of claim 6 , comprising:
11. After the step (2), (3) A step of heating and molding the obtained cellulose nanofiber-dispersed thermoplastic resin reinforced material under pressure. The method of claim 10 comprising:
12. The method according to claim 11, wherein the molding pressure in the step (3) is 5 MPa or more.
Citation Information
Patent Citations
Carbon short fiber reinforcement film and method for producing carbon short fiber reinforcement structure
JP2018012312A
Fiber reinforced resin composite material, laminate thereof, composition for fiber reinforced resin composite material, and method for producing fiber reinforced resin composite material
JP2019172797A
Method for producing intermediate base material and molded product made of composite material containing thermoplastic resin and reinforcing fiber, and intermediate base material and molded product
JP2020151969A
Industrial sheet material and method for manufacturing the same
JP2021049754A
Water repellent oil repellent agent and method for producing same, and water repellent oil repellent product and method for producing same
WO2019151040A1